A systematic review and meta-analysis of cross-sectional studies examining the relationship between mobility and cognition in healthy older adults - Demnitz, N; Esser, P; Dawes, H; Valkanova, V; Johansen-Berg, H; Ebmeier, K; Sexton, C (Elsevier, 2016)
Ageing is associated with declines in cognitive function and mobility. The extent to which this relationship encompasses the subdomains of cognition and mobility remains unclear, however. We searched MEDLINE and EMBASE databases for cross-sectional studies examining the association between objective mobility measures (gait, lower-extremity function, balance) and cognitive function (global, executive function, memory, processing speed) in healthy older adults. Of the 642 studies identified, 26 studies met the inclusion criteria, with a total of 26,355 participants. For each feature of physical mobility, the relation to each aspect of cognition was reviewed. In the context of each association, we summarised the results to date and performed random-effects meta-analyses of published data. Reviewed findings suggest that individuals with better mobility perform better on assessments of global cognition, executive function, memory and processing speed. Not all measures of mobility were equally associated with cognitive function, however. Although there was a larger number of gait and lower-extremity function studies, and this may have driven findings, most studies examining balance and cognition measures reported no significant results. Meta-analyses on reported associations supported results by revealing significant, albeit small, effect sizes in favour of a positive association between performance on mobility measures and cognitive assessments. Future research should aim to establish the mechanisms driving this relationship, as this may identify predictors of age-related impairments.